Unveiling Global Trends in Bioherbicide Research for Allelopathic Weed Control: A Bibliometric Analysis from 2002-2022 - Mohd Aridi, Nor Atirah; Yusoff, Nornasuha; Sahrir, Muhd Arif Shaffiq; Azizan, Kamalrul Azlan (AGRIVITA Journal of Agricultural Science, 2025)
The harmful effects of chemical herbicides on the environment and human health have increased interest in natural bioherbicides. This study analyzed global trends in bioherbicide research for controlling weeds from 2002 to 2022 using bibliometric analysis. The bibliometric analysis presented the research trend based on relevant research topics, an annual publication for 20 years, the co-occurrence of countries and institutions, productive journals, and frequent keywords used. The Scopus database resulted in 1472 articles analyzed using bibliometric tools, R-4.2.2 software with Bibliometrix-Biblioshiny, and VOSviewer 1.6.19. The number of publications on bioherbicides increased since 2002, with a sharp increase in the last two years. China was the most productive country, followed by the United States, Brazil, and Pakistan. The University of Agriculture in Pakistan and Fujian Agriculture and Forestry University in China were the most productive academic institutions. The most frequent keywords were "allelopathy," "bioherbicide," and "weed control." The co-occurrence analysis indicated that the United States collaborated the most with other countries. The findings suggest that bioherbicides with allelopathy as weed control have the potential to be an effective alternative to chemical herbicides. Besides, it provides insight for better-collaborated publication and potential networking in the future.